ANTIMICROBIAL COMPOSITIONS AND USES THEREOF - RAAD, Issam; ROSENBLATT, Joel (2022)
In some aspects, provided herein are antimicrobial compositions comprising partially esterified polygalacturonic acid and certain fatty acids (e.g., caprylic acid). In some embodiments, the antimicrobial composition may be administered (e.g., topically or orally) to a subject, such as a human patient to treat an infection (e.g., an infection comprising a biofilm). In some aspects, improved catheters are provided.